anonymous
  • anonymous
Fuctions!
Mathematics
chestercat
  • chestercat
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

anonymous
  • anonymous
Given the following functions f(x) and g(x), solve (f ⋅ g)(2) and select the correct answer below: f(x) = 2x2 − 10 g(x) = x + 9
anonymous
  • anonymous
a.) −22 b.) 22 c.) −66 d.) 66
anonymous
  • anonymous

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
(2(2)^2-10)(2+9) = -22
anonymous
  • anonymous
a)
anonymous
  • anonymous
Given the following functions f(x) and g(x), solve f[g(6)] and select the correct answer below: f(x) = 6x + 12 g(x) = x − 8
anonymous
  • anonymous
−96 0 24 48
anonymous
  • anonymous
0
Michele_Laino
  • Michele_Laino
hint: by definition of product of functions, we can write this: \[\Large \left( {f \cdot g} \right)\left( x \right) = f\left( x \right) \cdot g\left( x \right) = \left( {2{x^2} - 10} \right)\left( {x + 9} \right) = ...\]
anonymous
  • anonymous
6(6-8)+12 = 0
anonymous
  • anonymous
Given the following functions f(x) and g(x), solve (f/g)−3) and select the correct answer below: f(x) = 6x + 8 g(x) = x − 2
anonymous
  • anonymous
−2 −1/2 1/2 2
anonymous
  • anonymous
One more after that, then I'm done!!!
anonymous
  • anonymous
\[\frac{ 6(-3)+8 }{ -3-2 } = 2\] so d)
Michele_Laino
  • Michele_Laino
hint: \[\Large \left( {\frac{f}{g}} \right)\left( x \right) = \frac{{f\left( x \right)}}{{g\left( x \right)}} = \frac{{6x + 8}}{{x - 2}} = ...\]
anonymous
  • anonymous
Given the functions m(x) = 4x − 11 and n(x) = x − 10, solve m[n(x)] and select the correct answer below. m[n(x)] = 4x − 51 m[n(x)] = 4x − 29 m[n(x)] = 4x2− 51 m[n(x)] = 4x2 − 29
anonymous
  • anonymous
anonymous
  • anonymous
anonymous
  • anonymous
anonymous
  • anonymous
4x-40-11 = 4x-51 a)

Looking for something else?

Not the answer you are looking for? Search for more explanations.